Fostering Creative Thinking in Elementary Education: Integrating Social Inquiry Learning with Interactive Audio-Visual Media - Bahtiar, Reza Syehma; Jarmani, Jarmani; Putri, Ellena Aurellia; Aulia, Salwa Rizky; Widyaningrum, Rizky (Universitas Islam Lamongan, 2024)
This study investigates the integration of social inquiry learning with interactive audio-visual media to enhance creative thinking among primary school students. The study used a qualitative case study method, focusing on a Grade 5 class at SDN Jajartunggal III, Surabaya. Data collection methods included participatory observations, semi-structured interviews with teachers, and student artifacts analysis. The study sought to understand how this instructional Model affects fluency, flexibility, originality, and elaboration in students’ creative thinking. The findings revealed that interactive media, such as digital storytelling and animated simulations, significantly increased student engagement and facilitated creative problem-solving. Students were able to delve deeper into social issues, collaborate more effectively, and express creative ideas more confidently. The study also underscored the critical role of teachers in facilitating this integrated approach, as their ability to balance structured guidance with open-ended inquiry was key to fostering creativity. In conclusion, this study contributes to understanding how combining social inquiry learning with audio-visual media can enhance creativity in elementary education. The results highlight the importance of teacher facilitation and suggest that further study should investigate the long-term impacts of this pedagogical approach across different educational contexts.